ANALISIS DAMPAK MERGER TERHADAP KINERJA KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - DECKY PRIADI; SISSAH SISSAH; AHMAD SYAHRIZAL (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the effect of mergers on the financial performance of companies listed on the Indonesia Stock Exchange for the period 2017 - 2021. Financial performance in this research is measured using liquidity ratios (CR), leverage (DER), profitability (ROE), and activity (TATO ). This research uses quantitative methods, the samples used are 6 companies that have merged and are listed on the Indonesia Stock Exchange for the period 2017 - 2021. The parametric test used is the paired sample t test to answer the hypothesis. The results of this research show that there are no significant differences in the financial ratios CR, DER, ROE and TATO after the company merged. So the merger process carried out by the company does not show significant changes because post-merger synergies have not been achieved.